ANALISIS AKAR MASALAH PENYEBAB LAYANAN HOMECARE YANG BELUM BERJALAN OPTIMAL DI RS ‘X’ - aditya, luthfi (Jurnal Administrasi Publik, 2024)
Root Cause Analysis of Unoptimized Homecare Service in ‘X’ Hospital. Homecare is a revolutionary approach to healthcare, which allows patients to receive high-quality medical care without having to stay in the hospital. However, the data in 2022 shows that the number of patient visits per month reaches 3195 patients while the number of homecare patients per month is around 10 patients. This shows that there are still many patients who have not used homecare services. The study aims to identify factors that impact the ineffective implementation of homecare services. This study used semi-structural interviews and discussions with related units. Result of this study show factors that are the root problems studied in fishbone diagrams include human factors, methods, and machines. The conclusion of this study show that hospitals need to develop a plan of action to address these issues.